Does creatine supplementation hinder exercise heat tolerance or hydration status? A Systematic review with meta-analyses - Lopez, R. M.; Casa, D. J.; McDermott, B. P.; Ganio, M. S.; Armstrong, L. E.; Maresh, C. M. (Journal of Athletic Training, 2009)
Objective: To critically assess original research addressing the effect of creatine supplementation on exercise heat tolerance and hydration status. Data Sources: We searched the electronic databases PubMed, Scopus, Web of Science, SPORTDiscus, and Rehabilitation & Physical Medicine, without date limitations, for the following key words: creatine, exercise, thermoregulation, dehydration, hyperthermia, heat tolerance, exertional heat illnesses, and renal function. Our goal was to identify randomized clinical trials investigating the effect of creatine supplementation on hydration status and thermoregulation. Citations from related articles also were identified and retrieved. Data Synthesis: Original research was reviewed using the Physiotherapy Evidence Database (PEDro) Scale. One author initially screened all articles. Fifteen of 95 articles examined the effects of creatine on thermoregulation or hydration status (or both). Two independent reviewers then reviewed these articles. Ten studies were selected on the basis of inclusion and exclusion criteria. The PEDro scores for the 10 studies ranged from 7 to 10 points (maximum possible score = 10 points). Conclusions: No evidence supports the concept that creatine supplementation either hinders the body's ability to dissipate heat or negatively affects the athlete's body fluid balance. Controlled experimental trials of athletes exercising in the heat resulted in no adverse effects from creatine supplementation at recommended dosages.